MANAGEMENT STRATEGY OF MANGROVE ECOSYSTEM: A CONSIDERATION OF ECOSYSTEM SERVICES BY LOCAL USER AT BAROS - Mochammad Yenny; Boedi Hendrarto; Jafron W. Hidayat (COJ (Coastal and Ocean Journal), 2017)
Ecosystem management policies are complex and susceptible to social conflict because of uncertainty and many interests. The management policy without considering the mangrove ecosystem services is also believed to be one of the main factors causing the degradation of mangrove ecosystem. This research intends to formulate management strategy by considering the type of mangrove ecosystem services that is important according to the perspective of the community user. A total of 108 respondents were included in the survey. The results of PCA (Principal component analysis) showed that there were three main components formed with cumulative variance of 75,238%. The three components are physical ecological function which has the highest eigenvalue of 4,454 and 49,494% of variance, followed by tourism 14,150%, forest and fishery products 11,594%. The main components can be interpreted as a priority that can be used as the basis for management strategies. Therefore, an appropriate management strategy to be implemented based on these priorities is to harmonize the ecological functions and physical benefits of the processes that take place in the mangrove ecosystem with the use of educational based tourism. Keywords: management strategies, ecosystem services, perspectives, community users